2021
DOI: 10.1111/1348-0421.12937
|View full text |Cite
|
Sign up to set email alerts
|

The role of C/EBP homologous protein (CHOP) in regulating macrophage polarization in RAW264.7 cells

Abstract: Schistosomiasis is a zoonotic parasitic disease that is endemic in Asia. Macrophages are mainly involved in the inflammatory response of late schistosoma infection. Our previous study found that C/EBP homologous protein (CHOP) expression is significantly increased, and M2 macrophages are activated in schistosome‐induced liver fibrosis mice. However, the role of CHOP in the regulation of macrophage polarization remains to be further studied. Western blotting or quantitative PCR revealed that IL‐4 increased the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…To prove this, the target gene or protein was usually interrupted by an inhibitor/agonist, or knockdown/over-expressing [50,51]. AS, a STAT6-specific inhibitor, inhibits IL-4induced STAT6 activation in vitro and in vivo, thereby attenuating macrophage M2 polarization [52,53] and number [54]. AS was demonstrated by a decrease in Arg1, Fizz1, Ym1, and CD206 [55], which can attenuate the progression of tumors in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…To prove this, the target gene or protein was usually interrupted by an inhibitor/agonist, or knockdown/over-expressing [50,51]. AS, a STAT6-specific inhibitor, inhibits IL-4induced STAT6 activation in vitro and in vivo, thereby attenuating macrophage M2 polarization [52,53] and number [54]. AS was demonstrated by a decrease in Arg1, Fizz1, Ym1, and CD206 [55], which can attenuate the progression of tumors in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…TNF receptor associated factor 6 (TRAF6) is an important signaling node in the Toll-like receptor pathway, which can initiate the transcription of inflammation-related target genes ( 40 ). However, members of the CCAAT enhancer binding protein family and signal transducer and activator of transcription (STAT) family have been identified as key mediators of these responses ( 41 , 42 ). In addition, the regulators of lipid metabolism peroxisome proliferator-activated receptor γ, circular RNAs, microRNAs, and long noncoding RNAs have been shown to be key regulators of macrophage polarization in both in vitro and in vivo models ( 43 46 ) ( Figure 1 ).…”
Section: Characteristics Of Macrophages and Their Pathophysiological ...mentioning
confidence: 99%
“…Pretreatment with 10 mg/kg AS157499 1 h before ovalbumin challenge significantly suppressed hypercontractility of bronchial tissues, IL-13 production, and STAT6 phosphorylation [233]. More recently, several studies have evaluated AS157499 in the treatment of asthma and immune regulation [234][235][236][237]. In the context of cancer, Binnemars-Postma et al showed that STAT6 activation plays a critical role in M2 macrophage polarization [237].…”
Section: Stat6mentioning
confidence: 99%